Pengaruh Motivasi Kerja, Budaya Sekolah, dan Literasi Sekolah terhadap Kompetensi Profesional Kepala Sekolah Dasar Di Kecamatan Bodeh, Kabupaten Pemalang - Fajar Rahmadani; Nurkolis; Widya Kusumaningsih (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the influence of work motivation (X1), school culture (X2), and school literacy (X3) on the professional competence of elementary school principals (Y) in Bodeh District, Pemalang Regency. A quantitative causal approach was adopted using a questionnaire as the primary data collection instrument. The results show that work motivation, school culture, and school literacy each significantly influence principals’ professional competence, with respective contributions of 48.5%, 5.91%, and 42.0%. Simultaneously, the three variables explain 75.5% of the variance in principals’ professional competence. These findings indicate that strengthening work motivation, school culture, and school literacy is essential for enhancing the professional competence of school principals. The study provides practical implications for educational stakeholders, suggesting that principal development programs should focus on motivating school leaders, fostering collaborative school culture, and promoting literacy-based initiatives to support effective and innovative school leadership. Bodeh District, Pemalang Regency was chosen as the research location because it has a representative number of elementary schools and a diverse range of teacher and principal characteristics, allowing for a comprehensive analysis of work motivation, school culture, school literacy, and principals’ professional competence. In addition, the educational conditions in Bodeh District indicate a need for improving school leadership quality, making this study relevant for providing empirical insights useful for local education policy development.